Memahami Hadis Qailullah: Analisis Tekstual dan Kontekstual Atas Matan Qīlū Fa-Inna Al-Syayāṭīna Lā Taqīlu - Rayhan Arrasyid; Yulia Rahmi (CV. ALIM'SPUBLISHING, 2026)
This research is focused on the hadith of the Prophet PBUH about qailullah, which is a short break during the day recommended by the Prophet PBUH. The hadith emphasizes the importance of qailullah through the use of fi'il amr (commandment) in matan, and mentions that leaving it resembles the devil. The purpose of this research is to examine the validity of the hadith and understand its content textually and contextually so that its relevance in modern life can be known. The research uses a qualitative approach with library research methods and tahlili analysis. The textual approach is carried out through linguistic analysis and ushul rules, while the contextual approach is through historical, sociological, anthropological, and physiological analysis. The results of the study show that textually, qailullah means activities that are stopped from various activities, both with sleep and not sleeping. The mention of Satan is understood as a symbol of evil or misfortune, not a direct resemblance to a person who does not do qailullah. Contextually, the recommendation is related to the condition of the Arab community which has a hot climate and needs rest in the middle of activities. Thus, qailullah can be understood as a form of balance in activities, which is relevant to maintain the health, focus, and productivity of modern society.